Changes in Sleep-Wake Patterns and Disturbances Before and During COVID-19 in Urban American Indian/ Alaska Native Adolescents. Issue 3 (4th May 2022) - Troxel, Wendy M.; Palimaru, Alina I.; Klein, David J.; Dong, Lu; Dickerson, Daniel L.; Brown, Ryan A.; Johnson, Carrie L.; D'Amico, Elizabeth J.
ABSTRACT: Background: COVID-19 has profoundly affected sleep, although little research has focused on high-risk populations for poor sleep health, including American Indian/Alaska Native (AI/AN) adolescents. Methods: This is the first longitudinal study to examine changes in sleep with surveys completed before the pandemic and during the early months of COVID-19 in a sample of urban AI/AN adolescents (N = 118; mean age = 14 years at baseline; 63% female). We use a mixed-methods approach to explore how COVID-19 affected urban AI/AN adolescents' sleep, daily routines, and interactions with family and culture. Quantitative analysis examined whether pandemic-related sleep changes were significant and potential moderators of COVID-19's effect on sleep, including family and community cohesion and engagement in traditional practices. Results: : Findings demonstrate changes in sleep, including increases in sleep duration, delays in bedtimes and waketimes, and increases in sleep-wake disturbances ( p 's <.001). Higher levels of family cohesion and higher levels of engagement in traditional practices moderated pandemic-related increases in weekday sleep duration. Qualitative analyses revealed changes in adolescents' sleep and daily behaviors, as well as strategies adolescents used to cope with pandemic-related disruptions in sleep and routines. Conclusion: Findings demonstrate positive and negative changes in sleep during COVID-19 stay-at-home orders, including simultaneous increases in sleep duration and sleep-wake disturbances. Results highlight the importance of considering multi-level influences on adolescent sleep, such as early school start times, family dynamics, and cultural factors. A multi-level approach may help guide prevention and intervention efforts to improve adolescent sleep health.